Co3S4 porous nanosheets embedded in graphene sheets as high-performance anode materials for lithium and sodium storage1. Issue 13 (7th April 2015) - Du, Yichen; Zhu, Xiaoshu; Zhou, Xiaosi; Hu, Lingyun; Dai, Zhihui; Bao, Jianchun
<x xml:space="preserve">Abstract</x> A robust three-dimensional sandwich-like Co3S4 porous nanosheet/graphene sheet composite exhibits improved rate performance and cycling stability for both lithium and sodium storage.